English Word Stress in Polish Learners’ Speech Production and Metacompetence - Porzuczek, Andrzej; Rojczyk, Arkadiusz (Research in Language, 2017)
This paper focuses on the relations between conscious and subconscious aspects of English word stress acquisition. Using two tasks – reading and written word stress identification, we test metacompetence and production accuracy in the pronunciation of Polish learners, first year and third year English studies majors. The analysis of the collected data and correlations between the students’ metalinguistic knowledge and production accuracy, including error patterns and proportions, leads to conclusions concerning the significance of language awareness, learning experience and, indirectly, explicit didactic instruction for English word stress realization. Our results indicate that Polish learners tend to stress the word-initial syllable rather than the penult, typical of their native language. We have also observed a generally large, though smaller in more proficient learners, discrepancy between metacompetence and performance.